Faktor-Faktor Pemilihan Lokasi Hunian Perumahan Di Kecamatan Ungaran Barat - Annisa Rezita; Sri Rahayu (Teknik PWK (Perencanaan Wilayah Kota), 2017)
Ungaran Barat sub-district formed in 2005 the construction of Sub Ungaran Barat quite rapidly because it is crossed by the arterial road which connects Semarang-Solo-Yogyakarta makes development and regional development along the arterial road and a pretty rapid progression one development of housing. The development of housing in Ungaran Barat as the impact from the Semarang city developments away from the city centre and to the Administration that is out of bounds to Ungaran Barat. Ungaran Barat Sub-district currently is the target of the urban development especially in the field of housing currently ranging from simple residential, medium as well as the elite housing. The purpose of this study is to identify factors that affect housing residents to buy housing and inhabit in Ungaran Barat. The research method used is the quantitative quantitative methods, descriptive and factor analysis. Based on the results of the analysis, there are twelve factors that affect residents assessed in the selection of the location of residential housing that is quieteness, pollution-free, the view, the condition of clean water, electricity, security conditions, the status of ownership, type of housing units, home design, method of payment, income, house prices. Factor availability facilities and accessibility of housing within the means of votes not too affect residents since most residents can reach the outside of the housing with the use of private vehicles. Based on the analysis of the factors obtained six factors that affect residents in deciding to buy and inhabit the housing is a factor of social economy, then tersediaan means, the characteristics of the home and the environment, accessibility, comfort factors and factors of the condition of the infrastructure.